Kebijakan Pendidikan Di Indonesia - Abdul Rozak (Alim | Journal of Islamic Education, 2021)
This paper will describe the Education Policy in Indonesia, explain the meaning of policy, policy function, direction and characteristics of policies implemented in the implementation of regional autonomy. The approach used in this presentation is descriptive in nature with reference to the current law, the writings of education experts and appropriate theories. This presentation is expected to provide a brief overview of Education Policy in Indonesia which can then be used as a basis for more in-depth and comprehensive research. adjustments and changes with developments occurred in the era of society 5.0. Community involvement and increasing the role of schools is a necessity in education management so that the quality of graduates is better. School-Based Management (SBM) is one of the efforts to increase the role of schools and the surrounding community (stakeholders). The implementation of regional autonomy requires changes and adjustments so that the education process is more democratic, pays attention to diversity, regional and student needs and encourages increased community participation.